1999
DOI: 10.1074/jbc.274.37.26337
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Modulates β2-Adrenergic Receptor Palmitoylation and Signaling

Abstract: To determine whether nitric oxide (NO) modulates the ␤-adrenergic signaling pathway, we treated cells expressing ␤ 2 -adrenergic receptors (␤ 2 AR) with the NO donors, 3-morpholinosydnonimine (SIN-1) and 1,2,3,4-oxatriazolium,5-amino-3-(3-chloro-2-methylphenyl)-chloride and determined the intracellular production of cAMP after exposure to ␤-adrenergic receptor agonists, cholera toxin and forskolin. NO significantly decreased the potency of the ␤-adrenergic agonist, isoproterenol, to stimulate cAMP production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 54 publications
1
74
2
Order By: Relevance
“…The nitric oxide donor compound SIN-1 has also been reported to alter protein palmitoylation (60). As with SNC, the effects of SIN-1 on palmitoylation were protein-selective; palmitate incorporation into the transmembrane ␤-adrenergic receptor was reduced by SIN-1 treatment, whereas palmitate labeling of the G s ␣-subunit coupled to the receptor was unaffected (60).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The nitric oxide donor compound SIN-1 has also been reported to alter protein palmitoylation (60). As with SNC, the effects of SIN-1 on palmitoylation were protein-selective; palmitate incorporation into the transmembrane ␤-adrenergic receptor was reduced by SIN-1 treatment, whereas palmitate labeling of the G s ␣-subunit coupled to the receptor was unaffected (60).…”
Section: Discussionmentioning
confidence: 98%
“…The nitric oxide donor compound SIN-1 has also been reported to alter protein palmitoylation (60). As with SNC, the effects of SIN-1 on palmitoylation were protein-selective; palmitate incorporation into the transmembrane ␤-adrenergic receptor was reduced by SIN-1 treatment, whereas palmitate labeling of the G s ␣-subunit coupled to the receptor was unaffected (60). It thus appears that at least certain palmitoylated proteins, including Ha-Ras, are susceptible to nitrosylating agents but that each will display an individualized response, presumably resulting from regulatory mechanisms distinct from each protein.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lung has a well-developed antioxidant system (Rahman et al, 1996(Rahman et al, , 1997, overproduction of ROS or depression of the protective system results in epithelial cell damage, cell shedding, and bronchial hyperreactivity (Hulsmann et al, 1994;Cortijo et al, 1999). Studies with animal models have indicated that ROS contribute to airway hyperresponsiveness by increasing vagal tone due to damage of oxidant sensitive β-adrenergic receptors as well as decreasing mucociliary clearance (Owen et al, 1991;Adam et al, 1999). Consistent with these observations, our data have shown that generation of ROS in BAL cells was significantly increased after allergen challenge in OVA-inhaled mice and that administration of AD4 reduced the ROS generation and inhibited airway inflammation and hyperresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…AD4 was prepared as previously described (Adam et al, 1999;Bahat-Stroomza et al, 2005;Bartov et al, 2006). AD4 (60 or 120 mg/kg body wt/day), dissolved in PBS, was administered i.p.…”
Section: Administration Of Ad4mentioning
confidence: 99%
“…Wild-type human ␤ 2 AR, V2R, and hemagglutinin (HA)-tagged (YPYDVPDYA) ␤ 2 AR sequences were subcloned into a modified pcDNA3 vector (Invitrogen) in which the cytomegalovirus promoter was replaced by a Rous sarcoma virus promoter as described (8). V2R-GFP and ␤2AR-GFP.…”
Section: Methodsmentioning
confidence: 99%